Asymmetric effect of market sentiment on banking: A nonlinear ARDL approach - Nurhamizah Rashid,; Abdul Hafizh Mohd Azam,; Tamat Sarmidi,; Naziatul Aziah Mohd Radzi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the asymmetric impact of market sentiment on commercial bank deposits over long-run and short-run periods. Two attitude-based sentiments, the business condition index (BCI) and the consumer sentiment index (CSI) are used to proxy the market sentiment. By utilizing the Nonlinear Autoregressive Distributed Lag (NARDL) method on Malaysian data, the study found the existence of long-run and short-run asymmetric impact of market sentiment on bank deposit flow. Empirical results show that negative changes in market sentiment appear to affect bank deposits significantly in the long run while positive changes in the market sentiment show otherwise. This phenomenon would partially suggest that households might gone through a difficult phase such as job losses and rely on their saving to survive. Income and money supply, amongst other variables, demonstrate a long-run positive relationship with bank deposits, whereas interest rate has a long-run significant negative relationship. Results from NARDL also show that exchange rate, money supply, interest rate, income, and negative changes in BCI and CSI have a short-run effect on deposits. Overall, our study confirms the behavioural finance hypothesis which claims human behaviour affects financial decisions. The government should implement specific measures to reduce the impact of negative sentiment, as an increase in negative sentiment indicates households are likely to withdraw their deposit. Consequently, this phenomenon would affect household savings during their retirement age. Thus, the government should take the initiative or provide incentives to households during a hard time to cushion the impact of bad market sentiment.